ANALYSIS OF DIFFERENCES OF PRICE EARNING RATIO (PER) AND STOCK LIQUIDITY BEFORE (10 DAYS) AND AFTER (10 DAYS) STOCK SPLIT IN GO PUBLIC COMPANY IN INDONESIA STOCK EXCHANGE PERIOD 2009 – 2016 - Suharno, Hadi; Afriani, Afriani (EKONOMI BISNIS, 2021)
The purpose of this research is to know (1) difference of stock liquidity level before and after stock split (2) difference of Price Earning Ratio (PER) before and after stock split.The population used in this study are all companies listed on the Indonesia Stock Exchange. While the sample selection is taken by using purposive sampling method. The number of samples used by researchers are 62 companies listed on the Indonesia Stock Exchange and stock split in the period 2009-2016.Based on the results of research indicate that there is a significant difference in Price Earning Ratio (PER), either before stock split or Price Earning Ratio (PER) after stock split. With paired sample t-test results obtained t test with t count> t table (3.912> 2,000) can be concluded then Ho accepted means there is a difference between price earnings ratio (PER) of each sample company, either before stock split or price Earnings ratio (PER) after the stock split event.With paired sample t-test obtained t test results with t count> t table (1,844> 2,000) can be concluded then Ho accepted means there is no difference between the stock liquidity of each sample company, either before the stock split and the liquidity of stock after the event Stock split.